Footprints of climate change on Mediterranean Sea biota - Marbà, Núria; Jorda, Gabriel; Agusti, Susana; Girard, Coraline; Duarte, Carlos M. (Frontiers in Marine Science, 2015)
The Mediterranean Sea ranks among the ocean regions warming fastest. There is evidence for impacts of climate change on marine Mediterranean organisms but a quantitative assessment is lacking. We compiled the impacts of warming reported in the literature to provide a quantitative assessment for the Mediterranean Sea. During the last three decades the summer surface temperature has increased 1.15°C. Strong heat wave events have occurred in years 1994, 2003, and 2009. Impacts of warming are evident on growth, survival, fertility, migration and phenology of pelagic and benthic organisms, from phytoplankton to marine vegetation, invertebrates and vertebrates. Overall, 50% of biological impacts in the Mediterranean Sea occur at summer surface temperature anomaly ≤ 4.5°C and at summer surface temperature of 27.5°C. The activation energy (geometric mean 1.58 ± 0.48 eV), the slope of the Arrhenius equation describing the temperature-dependence of biological processes, for the response of Mediterranean marine biota to warming reveals that these responses in the Mediterranean are far steepest than possibly explained by the direct effect of warming alone. The observations are biased toward the northern and western sectors of the basin, likely underestimating the impacts of warming in areas where warming is particularly intense.